(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The scientific evaluation of medicinal plants used in the preparation of folk remedies has provided modern medicine with effective pharmaceuticals for the treatment of diseases. The ethanolic extract of Zanthoxylum armatum DC bark was investigated for its hepatoprotective and antioxidant effects on Paracetamol (500 mg/kg) induced acute liver damage in Wistar albino rats. Hepatoprotection activity was measured by using biochemical parameters such as serum glutamate oxalate transaminase and se-rum Glutamate Pyruvate Transaminase (SGOT and SGPT), alkaline phosphatase (ALP), bilirubin and total protein. The ethanolic extract of Zanthoxylum armatum DC(EZA) at the doses of (100 mg/kg ,200 mg/Kg and 400 mg/Kg) produced significant hepatoprotective effect by decreasing the activity of serum enzymes, bilirubin and lipid peroxidation while it significantly increased the levels of glutathione (GSH), catalyse (CAT) and super oxide dismutase (SOD) in a dose dependant manner. The effects of EZA were comparable to that of standard drug silymarin. These results suggest that EZA may have potential therapeutic value in the treatment of some liver disorders, probably by its antioxidative effect on hepatocytes.